2020
DOI: 10.1177/1178221820909352
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Misuse: Taking a Lifespan Perspective

Abstract: Prescription drug misuse (PDM), or medication use without a prescription or in ways not intended by the prescriber, is a notable public health concern, especially in the United States. Accumulating research has characterized PDM prevalence and processes, but age-based or lifespan changes in PDM are understudied. Given age-based differences in the medical or developmental concerns that often underlie PDM, it is likely that PDM varies by age. This review summarizes the literature on PDM across the lifespan, exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 172 publications
(368 reference statements)
7
33
0
Order By: Relevance
“…Internalizing and externalizing symptoms have been shown to partially mediate the association between ELS and prescription opioid misuse [ 24 , 106 ]. These findings suggest that self-medication may play a role in generating and maintaining both recreational and prescription opioid misuse in ELS-exposed individuals [ 124 , 125 ]. In addition to their euphoric and analgesic effects, opioids relieve stress through their inhibitory actions on the hypothalamic-pituitary-adrenal (HPA) axis [ 120 , 126 , 127 ], which can be highly negatively reinforcing [ 128 ] to individuals with such affective vulnerabilities.…”
Section: Evidence Of Els and Oud Associationsmentioning
confidence: 99%
“…Internalizing and externalizing symptoms have been shown to partially mediate the association between ELS and prescription opioid misuse [ 24 , 106 ]. These findings suggest that self-medication may play a role in generating and maintaining both recreational and prescription opioid misuse in ELS-exposed individuals [ 124 , 125 ]. In addition to their euphoric and analgesic effects, opioids relieve stress through their inhibitory actions on the hypothalamic-pituitary-adrenal (HPA) axis [ 120 , 126 , 127 ], which can be highly negatively reinforcing [ 128 ] to individuals with such affective vulnerabilities.…”
Section: Evidence Of Els and Oud Associationsmentioning
confidence: 99%
“…Of the remaining 172 full texts that were assessed for eligibility, 121 were excluded (see Figure 1 for details of selection process, and Table S2 for details of excluded references). Finally, 51 references were included 3,5–11,13–55 …”
Section: Resultsmentioning
confidence: 99%
“…For 27 (38.0%), misuse occurs when medicines are not used as prescribed (or medical misuse), 9,10,[15][16][17]21,23,26,27,33,34,38,43,55 when prescription-only medicines are used without prescription (or nonmedical misuse) 5,23,33,55 or both. 23,25,29,32,35,39,[50][51][52] In 14 definitions (19.7%), misuse occurs when initiators do not follow summary of product characteristics (SmPCs, i.e. off-label), medical guidelines or either.…”
Section: Definitions Of Medicine Misusementioning
confidence: 99%
“…While students’ motive to use prescription stimulants nonmedically for better performance while studying has been frequently reported in student samples of different ages (Faraone et al, 2020; Garnier-Dykstra et al, 2012; Rabiner et al, 2009; Schepis et al, 2020; Teter et al, 2020), parents’ willingness to initiate such behavior and the etiology behind their decision-making have rarely been studied. To the best of our knowledge, this is the first set of theory-driven research experiments investigating parents’ willingness to give CE to healthy children and the question of the drivers that lead parents to do so.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study among U.S. high school students found that 2.5% self-reported CE for study purposes (Teter et al, 2020). Among the several hundred thousand adolescents (aged 12–17) in the United States who misused prescription stimulants (Substance Abuse and Mental Health Services Administration, 2019), cognitive performance enhancement is one key motive (Schepis et al, 2020). The prevalence rates of CE that have been assessed in different populations (e.g., students or employed people) vary greatly (Maier & Schaub, 2015; Sattler, 2016; Smith & Farah, 2011).…”
Section: Introductionmentioning
confidence: 99%